Perinatal outcomes in women with lower-range elevated blood pressure and stage 1 hypertension: insights from the Kaya health and demographic surveillance system, Burkina Faso - Franck Garanet; Sékou Samadoulougou; Calypse Ngwasiri; Abou Coulibaly; Fatou B.Sissoko; Vincent N. Bagnoa; Adama Baguiya; Seni Kouanda; Fati Kirakoya-Samadoulougou (BMC, 2023)
Abstract Background The impact of lower thresholds for elevated blood pressure (BP) on adverse perinatal outcomes has been poorly explored in sub-Saharan African populations. We aimed to explore the association between lower BP cutoffs (according to the 2017 American College of Cardiology/American Heart Association [ACC/AHA] criteria) and adverse perinatal outcomes in Kaya, Burkina Faso. Methods This retrospective cohort study included 2,232 women with singleton pregnancies between February and September 2021. BP was categorized according to the ACC/AHA criteria and applied throughout pregnancy. A multivariable Poisson regression model based on Generalized Estimating Equation with robust standard errors was used to evaluate the association between elevated BP, stage 1 hypertension, and adverse perinatal outcomes, controlling for maternal sociodemographic characteristics, parity, and the number of antenatal consultations, and the results were presented as adjusted risk ratios (aRRs) with corresponding 95% confidence intervals (CIs). Results Of the 2,232 women, 1000 (44.8%) were normotensive, 334 (14.9%) had elevated BP, 759 (34.0%) had stage 1 hypertension, and 139 (6.2%) had stage 2 hypertension. There was no significant association between elevated BP and adverse pregnancy outcomes. Compared to normotensive women, women with elevated BP had a 2.05-fold increased risk of delivery via caesarean section (aRR;2.05, 95%CI; 1.08-3.92), while those with stage 1 hypertension had a 1.41-fold increased risk of having low birth weight babies (aRR; 1.41, 95%CI; 1.06-1.86), and a 1.32-fold increased risk of having any maternal or neonatal adverse outcome (aRR; 1.32, 95%CI; 1.02-1.69). Conclusions Our results suggest that the risk of adverse pregnancy outcomes is not increased with elevated BP. Proactive identification of pregnant women with stage 1 hypertension in Burkina Faso can improve hypertension management through enhanced clinical surveillance.